Aane Wala Hai: Waiting for the Arrival of the State. Issue 1 (1st March 2023) - Chatterjee, Syantani
Abstract: The Bharatiya Janata Party won the 2014 parliamentary elections in India, popularising the slogan ' Achhe din aane wale hai ' ('Good days are coming'). Even as the good days remained elusive, in 2019, the party won the popular vote again, with an additional promise of culling out putative 'infiltrators' from India by announcing 'NRC aane wala hai ' ('NRC is coming'). Drawing on ethnographic research carried out between 2016 and 2019 in a largely Muslim working-class neighbourhood next to one of Asia's largest garbage dumps in Mumbai, this article attempts to grasp the force of the state through its affective deferral by examining this aane wala hai form of governance – the forever-deferred, the always-arriving, the ready-to-strike – that is predicated upon weaponising deferral into a tactic of governance.